O Contra-Iluminismo do Marquês de Sade - Mattos, Elizângela Inocêncio (Universidade Federal de São Carlos, 2018)
This work aims to analyze the theoretical bases by which the Marquis de Sade built his philosophy, namely precisely the influence of La Mettrie and Holbach, which includes a study of nature and the mechanical question in the composition of beings, incurring to a fundamental determinism in the materialist current of the eighteenth century. It is important to understand how he took the thesis of mankind as a machine and the idea of a creative-destructive nature which allowed him to have a declared immoralism, based not only on nature, but also on militant atheism. The consequences of this path, incurs on the thesis of the counter-enlightenment of the Marquis de Sade who, man of his time, built a work based on combat, on denunciation, on the dominant discourse that characterizes the difference between strong and weak. The happiness demand is achieved by the total flow of passions, exploring all the dimensions of the corporal machine that can be happy, under the libertine optics, in the practice of crime. The way how Sade anticipates on treating evil as a component of nature, source of pleasure, also results in the intolerance of the libertine towards the victim.